New development: Learning communities—an approach to dismantling barriers to collective improvement. Issue 4 (19th May 2023) - Wilson, Louise; Hawkins, Melissa; French, Max; Lowe, Toby; Hesselgreaves, Hannah
IMPACT: Financial, performance and workload pressures on public services are increasing. Methods which enable practitioners to pool together and reflect on 'practical wisdom' to make better decisions in the navigation of complexity have the potential to improve the practitioner and service user experience and enable more effective targeting of resource-intensive interventions. This article contributes to the improved understanding of the practicalities, limitations and opportunities of surfacing and sharing tacit knowledge in the public sector environment. It will be of value to healthcare and social care practitioners, commissioners, service managers, educationalists and organizational development leads.